Monitoring the Distribution of Engerix B Vaccine Storage at the Pediatric Polyclinic in X Hospital, West Jakarta in March 2023 - M. ARPEN; Milda Rianty Lakoan (An-Najat, 2023)
Distribution is a series of activities in order to distribute/deliver pharmaceutical preparations, medical devices, and consumable medical materials from storage to service units/patients while ensuring quality, stability, type, quantity, and timeliness1. In vaccine distribution, it is necessary to pay attention to the temperature in the container used to carry the vaccine, so as to maintain the quality of the vaccine during transportation by paying attention to the provisions for the use of cold/cool boxes, vaccine carriers, cold pack thermoses, and cool packs. The vaccine temperature must be kept stable between 2oC and 8oC to keep the vaccine in good condition. The purpose of this study was to determine the distribution of Engerix B vaccine storage in the pediatric polyclinic of X Jakarta Barat Hospital to ensure safety to patients. The method used in the research is descriptive qualitative by means of observation, where direct observation of ongoing activities is carried out. The results obtained according to the initial temperature of vaccine storage obtained a percentage of 100%, the final temperature of vaccine storage during distribution obtained a percentage of 12.5%, and for the completeness of the distribution tool obtained a percentage of 100%. It can be concluded that what is not in accordance with the regulations of the Ministry of Health is the final temperature of the vaccine during distribution with a percentage of 12.5% very poor criteria.